Analisis Perbedaan Keterikatan Kerja Karyawan Milenial dan Faktor yang Mempengaruhi pada Karyawan BUMN di Indonesia - Widyantoro, Harry; Nurhadi, Mochamad; Rachmat, Basuki (Jurnal Ilmu Manajemen, 2024)
This study aims to explore the differences in Employee Engagement in millennial employees of PT. Infomedia Nusantara are based on gender differences with Employee Job Satisfaction and Job Resilience being factors that influence employee work engagement with gender moderation. The sampling technique used a saturated sample method on all millennial employees at PT Infomedia Nusantara (Telkom Group) with 126 respondents. The research instrument uses a Likert scale of 1 to 7 which is tested for validity and reliability to ensure that the instruments used in the study are valid and reliable. The analysis technique uses a Structural Equation Model with Partial Least Square (SEM-PLS). The results showed that Employee Resilience and Millennial Employee Satisfaction of PT. Infomedia Nusantara were able to positively influence Employee Engagement, while gender differences did not moderate the influence between resilience and job satisfaction on job attachment.